“How ‘ya gonna keep’em down at the farm now that they’ve seen Paree?”: France in Super Hero Comics - Nicolas Labarre (Transatlantica)
Any extensive reading of super hero comics will reveal that the representation of France within the genre borrows mostly from touristic clichés, using the country as a foreign, exotic yet not too disorientating setting. Narrative economy and gradual refinements have led to the creation of a codified, consensual and unrealistic depiction of France, centered mostly on Paris and the Eiffel Tower. However, this efficient codification is not value-free. A study of Justice League Europe, a rare example of super-hero series set in France over a long period reveals that France is consistently depicted as a place of history, while being denied a contemporary significance. The country appears as a fascinating but subordinate neighbor, and this evaluation can in turn be found, albeit in a more elliptic way, in numerous series portraying France only in short episodes. The self-consciousness of modern super hero comics, however, suggests that the notion of representation should be handled with care. The depiction of France in super-hero comics originates in part in the perception of the country in the United States, but it also derives in a significant way from the internal evolutions of the genre.